2015
DOI: 10.1001/jamaoto.2014.2926
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events and Discomfort During Magnetic Resonance Imaging in Cochlear Implant Recipients

Abstract: Even with protective head bandages, 1.5-T MRI in patients with CIs led to a variety of adverse events, including discomfort or pain and displacement of the internal magnet. Therefore, sedation and careful head positioning may be appropriate for some patients with CIs who undergo MRI, and these patients should be carefully monitored to decrease the likelihood of such adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 17 publications
1
100
0
1
Order By: Relevance
“…Kim et al retrospectively reviewed CI recipients and found five of 18 CI patients (28%) and five of 30 MRI scans (17%) had complications while undergoing MRI despite a head wrap. All five had significant pain limiting ability to complete their MRI, one of which had magnet displacement, one with magnet polarity reversal, and one necessitating the OR for magnet removal . In a separate series, Carlson et al retrospectively reported that four of 16 patients (25%) undergoing total 34 MRI scans had complications: one patient with two separate episodes of magnet polarity reversal, three with canting of the magnet, and two with significant pain requiring trip to the OR for magnet removal .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kim et al retrospectively reviewed CI recipients and found five of 18 CI patients (28%) and five of 30 MRI scans (17%) had complications while undergoing MRI despite a head wrap. All five had significant pain limiting ability to complete their MRI, one of which had magnet displacement, one with magnet polarity reversal, and one necessitating the OR for magnet removal . In a separate series, Carlson et al retrospectively reported that four of 16 patients (25%) undergoing total 34 MRI scans had complications: one patient with two separate episodes of magnet polarity reversal, three with canting of the magnet, and two with significant pain requiring trip to the OR for magnet removal .…”
Section: Discussionmentioning
confidence: 99%
“…Four of five patients who experienced MRI‐related complications had the wrap in place; eight had recorded use; and nine were not recorded in the electronic medical record and were noted as “unknown” (Table ). There are multiple patient series and case reports of CI MRI‐related complications with the head wrap in place . Prior to the introduction of the head wrap, the first studies that pioneered MRI safety and approval were done in CI systems in which the magnets were embedded within the device.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 A recent study observed that an MRI scan can cause pain, magnet displacement, and polarity reversal of the magnet and surgery may be required for removal and reinsertion of the magnet. 9 External components of the implant should be removed during MRI scans, gamma camera and radiotherapy with cobalt units/linear accelerator. 4,6 Patients' cochlear implant teams should be consulted before these procedures.…”
Section: Cochlear Implant Updatementioning
confidence: 99%